Terminological recommendations for software localization - Schmitz, Klaus-Dirk (Language at Work - Bridging Theory and Practice, 2009)
After an explosive growth of data processing and software starting at the beginning of the 1980s, the software industry shifted toward a strong orientation in non-US markets at the beginning of the 1990s. Today we see the global marketing of software in almost all regions of the world. Since software is no longer used by IT experts only, and since European and national regulations require user interfaces, manuals and documentation to be provided in the language of the customer, the market for software translation, i.e. for software localization, is the fastest growing market in the translation business.